From Charity to Justice: Revisited. (April 2015) - Thacker, Justin
At least since the 1990s, some theologians and development practitioners have been calling for greater attention to be paid to issues of structural injustice in respect of the global poor. With an increasing number of voices critiquing current models of aid and development, the imperative to pay greater attention to such advocacy or justice based initiatives is even more relevant. In this article, I explore why evangelicals in particular have been reticent about such moves from 'charity to justice' and I make a series of biblical, theological and sociological arguments as to why we should do so.